Occupational Therapists’ Perceived Confidence in the Management of Concussion: Implications for Occupational Therapy Education - Christina Finn (Occupational Therapy International)
The purposes of this study were to examine occupational therapists’ perceived confidence in the treatment and assessment of patients who have sustained concussion, to determine what factors are associated with higher versus lower levels of confidence, and to determine if concussion was a topic covered in occupational therapy curricula. This study utilized an electronic questionnaire sent out to occupational therapists in all areas of practice through social media, AOTA discussion forums, and through a continuing education company. Results indicate that there is variability in occupational therapists’ perceived confidence in evaluation and treatment for individuals who have sustained concussion. Chi-square analysis indicates that higher levels of perceived confidence are associated with more clinical experience and greater amounts of continuing education in the area of concussion. Occupational therapists may benefit from additional training and education in the area of concussion.